2020
DOI: 10.3390/en13020441
|View full text |Cite
|
Sign up to set email alerts
|

Research Review of a Vehicle Energy-Regenerative Suspension System

Abstract: Vehicles are developing in the direction of energy-saving and electrification. suspension has been widely developed in the field of vehicles as a key component. Traditional hydraulic energy-supply suspensions dissipate vibration energy as waste heat to suppress vibration. This part of the energy is mainly generated by the vehicle engine. In order to effectively utilize the energy of this part, the energy-regenerative suspension with energy recovery converts the vibrational energy into electrical energy as the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 54 publications
0
7
0
Order By: Relevance
“…The energy recovery system not only recovers vibration energy, but also converts it into electrical energy that can be stored in batteries as a source of power. Since the idea of energy recovery was intensified in the last century, energy efficiency has gained in importance in the automotive industry, the research of suspensions with energy recovery systems was revived to [47].…”
Section: Energy Of Damper Vibrationmentioning
confidence: 99%
“…The energy recovery system not only recovers vibration energy, but also converts it into electrical energy that can be stored in batteries as a source of power. Since the idea of energy recovery was intensified in the last century, energy efficiency has gained in importance in the automotive industry, the research of suspensions with energy recovery systems was revived to [47].…”
Section: Energy Of Damper Vibrationmentioning
confidence: 99%
“…Work [12] assesses the potential of recuperation systems of the energy absorbed by a vehicle's suspension DD; it was recognized to be large. It has been shown that the energy efficiency of such recuperation systems is on average 50 %.…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%
“…Compared with the traditional passive suspension, the active suspension can improve the smoothness and handling stability of the vehicle. For the problem of high energy consumption of active suspension, the use of the electromagnetic induction principle to recover the energy of suspension vibration is not only important for improving the comfort but also the fuel economy of the vehicle [4,5].…”
Section: Introductionmentioning
confidence: 99%